Combination of radiation therapy for brain metastasis and anti-PD-1/PD-L1 treatment in non-small cell lung cancer: two cases and review of the literature. Issue 4 (9th February 2021) - Nigro, Olga; Tuzi, Alessandro; Coppola, Andrea; Tartaro, Tiziana; Chini, Claudio; Pinotti, Graziella
Abstract : Lung cancer is the most frequent cause of cancer-related death worldwide and is usually diagnosed in advanced stages. Among those, approximately 7.4% of non-small cell lung cancer (NSCLC) patients will have brain metastasis (BM) at presentation, and 25–30% will develop BM during the course of their disease. To date, patients with BMs are increasingly considered for combined treatment using systemic immune checkpoint inhibition (ICI) and cranial radiation therapy (RT); yet, there is limited data regarding the safety of this approach. Here, we report two cases of NSCLC patients treated with two different types of cranial RT and ICIs.